Hysteresis and bistability in synaptic transmission modeled as a chain of biochemical reactions with a positive feedback - Katauskis, Pranas; Ivanauskas, Feliksas; Alaburda, Aidas (Nonlinear Analysis: Modelling and Control, 2024)
In this paper, we employ computational analysis to investigate the long-term potentiation (LTP) and memory formation in synapses between neurons. We use a mathematical model describing the synaptic transmission as a signal transduction pathway with a positive feedback loop formed by diffusion of nitric oxide (NO) to the presynaptic site. We found that the model of synaptic transmission exhibits a hysteresis-like behavior, where the strength of synaptic transmission depends not just on instantaneous interstimulus intervals, but also on the history of activity. The switching between resting and memory states can be induced by physiologically relevant and moderate (less than 50%) changes in the duration of interstimulus intervals.
Keywords: long-term potentiation; memory; modeling; positive feedback loop; bistability; hysteresis-like behavior; information processing